2014
DOI: 10.1097/id.0000000000000110
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Surface Modified Zirconia Implants With Commercially Available Zirconium and Titanium Implants

Abstract: The results suggest that the new implants comparably osseointegrate within the healing period, and they have a good in vivo biocompatibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0
8

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 35 publications
0
18
0
8
Order By: Relevance
“…Consequently, the correlations found were very high. The minipig intra-oral model is known to represent a fully functional in-vivo anatomical model for dental implant placement and it has been increasingly used to assess the performance of dental implants [15,27,28]. In this study the encountered bone was rather dense and only 29 out of 134 osteotomies and implants were included in the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the correlations found were very high. The minipig intra-oral model is known to represent a fully functional in-vivo anatomical model for dental implant placement and it has been increasingly used to assess the performance of dental implants [15,27,28]. In this study the encountered bone was rather dense and only 29 out of 134 osteotomies and implants were included in the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Surface modification can enhance bone healing and integration of titanium implants and result in higher bone-implant contact ratios [20, 31]; however, the interfacial interaction of modified zirconia with bone is still not fully understood. A number of animal studies have been published that outline hard and soft tissue integration of zirconia implants on the histological level and have shown promising results [29, 32, 33]. Further, cell culture studies have demonstrated that zirconia especially with a moderately rough surface is accepted by osteoblasts and integrates into bone tissue [9, 34].…”
Section: Discussionmentioning
confidence: 99%
“…By far, histomorphometric analysis has been the gold standard in evaluating the bone-implant interface. The various methods of the histomorphometric analysis, microscopic magnification, and different software and algorithms appear to play a crucial role in BIC calculations which may subsequently lead to deviant results [29, 32]. The bone tissue has to be transferred to specialized laboratory for preparation immediately after animal sacrifice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Osseointegration has been established as a healing period that involves cellular and extracellular events and is characterized by the creation of structural and functional connections between the bone and the surface of the implant. 1,13,33 Different methodologies have been developed to evaluate the interaction between the bone and the implant surface. 13,34 In this way, osseointegrations of M-Y-TZP, M-Ti and RBM-Ti were evaluated by micro-CT, histomorphometry and fluorochrome labeling analyses.…”
Section: Discussionmentioning
confidence: 99%